Development of an estimation model for the evaluation of the energy requirement of dilute acid pretreatments of biomass. (January 2015) - Mafe, Oluwakemi A.T.; Davies, Scott M.; Hancock, John; Du, Chenyu
Abstract: This study aims to develop a mathematical model to evaluate the energy required by pretreatment processes used in the production of second generation ethanol. A dilute acid pretreatment process reported by National Renewable Energy Laboratory (NREL) was selected as an example for the model's development. The energy demand of the pretreatment process was evaluated by considering the change of internal energy of the substances, the reaction energy, the heat lost and the work done to/by the system based on a number of simplifying assumptions. Sensitivity analyses were performed on the solid loading rate, temperature, acid concentration and water evaporation rate. The results from the sensitivity analyses established that the solids loading rate had the most significant impact on the energy demand. The model was then verified with data from the NREL benchmark process. Application of this model on other dilute acid pretreatment processes reported in the literature illustrated that although similar sugar yields were reported by several studies, the energy required by the different pretreatments varied significantly. Highlights: We developed a model for energy requirement evaluation for pretreatment processes. NREL dilute acid pretreatment process was used as an example. Around 1692 kJ kg −1 energy need to be supplied in order to carry out pretreatment. The majority of the energy required was from the heating stage. Solid loading rate was the key factor in influencing the energy requirements.